2014
DOI: 10.1080/10408398.2012.720619
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Mycotoxins in Food and Feed Products in Portugal and Estimation of Probable Daily Intakes

Abstract: Mycotoxins are toxic secondary metabolites produced by filamentous fungi that occur naturally in agricultural commodities worldwide. Aflatoxins, ochratoxin A, patulin, fumonisins, zearalenone, trichothecenes, and ergot alkaloids are presently the most important for food and feed safety. These compounds are produced by several species that belong to the Aspergillus, Penicillium, Fusarium, and Claviceps genera and can be carcinogenic, mutagenic, teratogenic, cytotoxic, neurotoxic, nephrotoxic, estrogenic, and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 84 publications
1
75
0
2
Order By: Relevance
“…This result agrees with other publications where low levels of OTA were also detected in Portuguese wines (Festas et al, 2000;Pena, Cerejo, Silva, & Lino, 2010;Ratola, Martins, & Alves, 2004). According to Abrunhosa et al (2016), the levels found by several authors range from 0.002 to 2.4 µg L −1 , with only two wines having OTA above the EU legal limit.…”
Section: Application Of Bsa-agarose Spe Of Ota Determination In Winessupporting
confidence: 92%
See 1 more Smart Citation
“…This result agrees with other publications where low levels of OTA were also detected in Portuguese wines (Festas et al, 2000;Pena, Cerejo, Silva, & Lino, 2010;Ratola, Martins, & Alves, 2004). According to Abrunhosa et al (2016), the levels found by several authors range from 0.002 to 2.4 µg L −1 , with only two wines having OTA above the EU legal limit.…”
Section: Application Of Bsa-agarose Spe Of Ota Determination In Winessupporting
confidence: 92%
“…Wine is a widely consumed beverage and represents one of the biggest sources of OTA daily intake in some countries (Miraglia & Brera, 2002). For example, in Portugal, wine contributes for 8% of the probably daily intake of OTA (Abrunhosa et al, 2016). Thus, the European Commission fixed the regulatory limit of OTA in wine, grape juices and grape beverages at 2 μg Kg −1 (EC, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Analytical techniques such as thin-layer chromatography [6], high-performance liquid chromatography (HPLC) [7][8][9][10], and enzyme-linked immunosorbent assay (ELISA) have been available for the qualitative and quantitative analysis of AFB2 [11]. Although HPLC is the most commonly used method, because it offers high sensitivity and selectivity, it has some limitations in terms of costs incurred by the sophisticated equipment and the methods are not cost-effective, requiring a relatively long analysis time, so they are neither readily available in developing countries nor capable of on-site detection.…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins occur particularly in regions or countries with climates of high temperature and humidity or where there are poor crop harvesting and storage conditions, which encourage mould growth and mycotoxin development (25). The toxic effects of mycotoxins are mainly on liver and they cause teratogenic, mutagenic, immunosuppressive, carcinogenic, cytotoxic, neurotoxic, nephrotoxic and oestrogenic effects (3,21). These toxins may show no clinical symptoms unless they are with secondary bacterial infections and high rate of mortality.…”
Section: Introductionmentioning
confidence: 99%